Prevalence and Outcome of Operative Vaginal Delivery among Mothers Who Gave Birth at Jimma University Medical Center, Southwest Ethiopia. (9th July 2018) - Hubena, Zenebe; Workneh, Ahadu; Siraneh, Yibeltal
Abstract : Background. Operative vaginal deliveries (OVD) are vaginal deliveries accomplished with the use of a vacuum device or forceps. If it is technically feasible and can be safely accomplished, termination of second stage labor by operative vaginal delivery is indicated in any condition threatening the mother or fetus that is likely to be relieved by delivery. Hence, the objective of this study is to assess the prevalence, common indication, outcome, and associated factors of operative vaginal delivery among mothers who gave birth in Jimma University Medical Center (JUMC). Method. A facility-based cross-sectional study design was used in maternity ward on 242 mothers who gave birth by operative vaginal delivery from December 01, 2016, to May 30, 2017. The clinical data were collected using a check list, recordings of intrapartum fetal and maternal state, and immediate fetomaternal outcomes. The study participants were recruited using consecutive sampling method. Sociodemographics and related data were collected at exit using structured interviewer administered questionnaire which was developed by reviewing different literature and the remaining information abstracted from patient charts. Data were entered to Epidata 3.1 and exported to SPSS version 21 for analysis. Bivariate analysis was done to identify candidate variables using p<0.25. Multivariable logistic regression was used to control the effect of confounding variables and to identify factors affecting the fetomaternal outcome. Statistical significance was declared at P<0.05 using adjusted OR with 95% CI. Result. Out of the 2348 pregnant mothers who gave birth in the labor ward of JUMC during the 6 months of the study period, 242 (10.3%) were by operative vaginal delivery (OVD). The commonest indication for operative vaginal delivery is found to be nonreassuring fetal heart rate pattern, 136 (56.2%). Out of all neonates delivered by operative vaginal delivery 210 (86.8%) had favorable outcome. Of all mothers who gave birth by operative vaginal delivery 232 (95.9%) had favorable outcome. Type of instrument used for operative vaginal delivery (AOR=0.228, 95%CI: 0.078, 0.671) and presence of grade two (AOR=0.163, 95%CI: 0.031, 0.858) and grade three (AOR=0.088, 95%CI: 0.024, 0.327) meconium stained amniotic fluid are factors affecting neonatal outcome while neonatal birth weight (AOR=0.007, 95%CI: 0.000, 0.151) is factor affecting maternal outcome of operative vaginal delivery. Conclusion. Prevalence of operative vaginal delivery is found to be 10.3% with the commonest indication of nonreassuring fetal heart rate pattern. Nearly all of mothers and neonates had favorable outcome. Type of instrument applied for operative vaginal delivery is the strongest predictor of neonatal outcome while neonatal birth weight is the only predictor of maternal outcome identified in this study.